Mapping the Development of Christology and Contextual Theology in Papua: A Systematic Literature Review (2014–2024) - Evelien Fitri Ugadje (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2025)
This study examines the development of Christology and contextual theology in Papua over the past decade and its implications for academic discourse, church practice, and the strengthening of inclusive theology. The research employed a Systematic Literature Review (SLR) with the PRISMA protocol, analyzing 33 journal articles published between 2014 and 2024 that explicitly addressed the Papuan context. Data were collected from national and international academic databases and analyzed thematically to map trends, methodological approaches, and research gaps. The findings show that contextual theology in Papua is dominated by qualitative approaches, particularly case studies and literature studies, with a strong focus on integrating Christian faith and local cultural symbols. Four main patterns were identified: symbolic Christology, relational Christology, contextual-liberation Christology, and early signs of ecological Christology. The production of theological knowledge is concentrated in highland communities and institutions such as STFT GKI I.S. Kijne Jayapura, while coastal, southern, and western regions remain underrepresented. Contextual Christology addressing suffering, spirituality, and social identity also remains underexplored. The implications highlight the need for a more inclusive contextual theology that integrates local values, cultural rituals, and interfaith dialogue. Practically, the study recommends reforming theological curricula based on local culture, developing contextual liturgical practices, and strengthening interdisciplinary collaboration to enhance the church’s role as an agent of social transformation. The originality of this study lies in its systematic mapping of previously fragmented literature, providing a more structured framework rooted in the lived faith experiences of Papuan communities while enriching global theological discourse.